2021
DOI: 10.1017/s2040174420001403
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: can we treat the mother without harming her baby?

Abstract: Medical care is predicated on ‘do no harm’, yet the urgency to find drugs and vaccines to treat or prevent COVID-19 has led to an extraordinary effort to develop and test new therapies. Whilst this is an essential cornerstone of a united global response to the COVID-19 pandemic, the absolute requirements for meticulous efficacy and safety data remain. This is especially pertinent to the needs of pregnant women; a group traditionally poorly represented in drug trials, yet a group at heightened risk of unintende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 144 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…25 Angiotensin converting enzyme 2, a target of SARS-CoV-2 cell entry, and the spike glycoprotein of SARS-CoV2 have been found on the syncytiotrophoblast cells of the placental villi that form the interface between mother and fetus in the placenta. 29 Therefore, vertical transmission may be possible, unlike with SARS, where no evidence of vertical transmission exists, but it is unclear whether these 19 cases were infected in utero, intrapartum or postpartum. 25 This study by Pettirosso et al also states that the risk of vertical transmission was assessed with rtPCR of nasopharyngeal secretions, placenta, cord blood, amniotic fluid and breastmilk.…”
Section: Vertical Transmission Likelihoodmentioning
confidence: 99%
“…25 Angiotensin converting enzyme 2, a target of SARS-CoV-2 cell entry, and the spike glycoprotein of SARS-CoV2 have been found on the syncytiotrophoblast cells of the placental villi that form the interface between mother and fetus in the placenta. 29 Therefore, vertical transmission may be possible, unlike with SARS, where no evidence of vertical transmission exists, but it is unclear whether these 19 cases were infected in utero, intrapartum or postpartum. 25 This study by Pettirosso et al also states that the risk of vertical transmission was assessed with rtPCR of nasopharyngeal secretions, placenta, cord blood, amniotic fluid and breastmilk.…”
Section: Vertical Transmission Likelihoodmentioning
confidence: 99%
“…Ghema et al [ 18 ] and Crovetto et al [ 35 ] found through their fetal studies other less frequent complications such as perinatal asphyxia, respiratory failure, multi-organ dysfunction, brain damage, malformation, intrapartum fetal distress, and even death. Another complication in children of COVID-19-infected pregnant women, though rare, is a neonatal inflammatory syndrome whose clinical manifestations are elevated inflammatory biomarkers, organ dysfunction, and in some cases myocardial dysfunction [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were also conducted on the breast milk of those mothers who were infected, as breast milk could be a mechanism of transmission to the neonate; however, these indicated that it was the close contact of the neonate with its mother that caused the infection, as no evidence of SARS-CoV-2 RNA or protein was found in breast milk [ 27 ]. However, studies suggest that the mechanisms involved in maternal–fetal transmission are unclear and that transmission is probable, but the incidence is extremely low [ 33 ] and most are acquired at delivery or postpartum [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant women are a traditionally poorly represented group in drug studies, but a high-risk group with regard to unwanted maternal-fetal events because of the unique physiology of pregnancy with implications for fetal and neonatal drug exposure. However, given the complexity of participation in drug trials during pregnancy, many clinical drug trials exclude pregnant women [ 46 ].…”
Section: Resultsmentioning
confidence: 99%